(untitled) (The Pakistan Development Review, 2013)
With urbanisation1 and modernisation of the economy, the use of electrical appliances has increased manifold in Pakistan. Now, household shares in the total electricity use account for 46.5 percent. While other users have lower shares that are industrial 27.5 percent, agriculture 11.6 percent, commercial 7.5 percent and the government 6.2 percent only [Pakistan (2012-13)]. Overtime, the household electricity consumption has also increased because of the increase in electricity consumers2 and of village electrification.3 Other important reasons include the use of modern appliances including both locally made and smuggled and increase in the share of urban women in the labour force by 6.5 percent during 2007-08 and 2012- 13 [Pakistan (2012-13)]. These reasons are also responsible for enlarging electricity demand and supply gap over the years and have led to the electricity shortage to alarming proportions in March 2012. The electricity gap increased to 57,754 GW from 56,930 GW showing an increase of 1.4 percent from the corresponding period of the last year. The acute electricity shortage has caused long hours of the electricity load shedding in the country. The population living in urban areas bears the direct fall out of the electricity breakdown because of the modern lifestyle and sheer dependence on electricity [Pakistan (2012-13)].